Ribonucleic Acid Synthesis in Cells Infected with Herpes Simplex Virus VI. Polyadenylic Acid Sequences in Viral Messenger Ribonucleic Acid - Bachenheimer, Steven L. (1972)
Evidence is presented by use of radiolabeling and pancreatic and T1 ribonuclease digestion that some of the ribonucleic acid specified by herpes simplex virus contains polyadenylic acid sequences. The polyadenylic sequences are not transcribed from viral DNA.